The development of an education management information system from a sensemaking perspective and the application of quantitative methods to analyse education data sets - Van Wyk, Christoffel (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Education Policy Studies))--University of Stellenbosch, 2006.